Analysis of content validity of multiple choice questions for the odd semester final exam made by English subject teachers for class 11 at SMK NU 1 Karanggeneng 2022/2023 - ainni, nurul (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2024)
The evaluation of learning plays a vital role in enhancing the quality of education. Effective evaluation methods help measure students' understanding, identify individual needs, and adapt teaching strategies. In the context of Vocational High Schools (SMK), the end-of-semester examination serves as an important evaluation component. This study focuses on analyzing the content validity of multiple-choice questions in the English final semester examination at SMK NU 1 Karanggeneng during the 2022/2023 academic year. The writers employed a descriptive qualitative research approach, utilizing documentation as the primary method. The data collected from SMK NU 1 Karanggeneng were systematically analyzed to assess the alignment between the examination questions and the basic competency standards of the 2013 curriculum(KEMENDIKBUT 2013). The findings revealed that all 60 multiple-choice questions were aligned with the basic competency standards, except for the topic of text biography. This study emphasizes the significance of conducting content validation to ensure accurate evaluation results and provides insights for improving future examination content. Overall, the research contributes to enhancing the effectiveness of learning evaluation methods in SMK.